Prasangka & konflik : komunikasi lintas budaya masyarakat multikultur - Liliweri, Alo, 1957- (Yogyakarta : LKiS, 2005)
Cultural identity and multiculturalism related to ethnic and social conflict, analysis and resolution in Indonesia.
Includes bibliographical references (p. [407]-434) and index.
Keywords: Intercultural communication -- Indonesia; Indonesia -- Ethnic relations